Understanding enabling Levers of Control (LOC) in Malaysian Local Government Authorities (LGAs): the case of LGKV and LGER / Azmi Aminuddin - Aminuddin, Azmi (Institute of Graduate Studies, UiTM, 2016)
Malaysian LGAs (Local Government Authorities) are expected to establish high quality urban, social and recreation services; provide opportunities for uniform economic growth; be strong and able to contribute to the establishment of a progressive society and a clean and healthy environment. The new public sector management reforms movement has highlighted the importance that authorities use an appropriate MCS (Management Control System) as well as both financial and nonfinancial performance measurement in order to improve the ineffectiveness and inefficiency that was previously reported. By employing an inductive comparative case study using qualitative research techniques, the implementation of LOC (Levers of Control) and LOC:SSRPBT Star Rating System was investigated in two selected Malaysian LGAs: LGKV and LGER. Using Institutional Theory as the underpinning theory, the phenomena of change that take place towards the implementation was also identified. The study found that there was a close connection between LOC and SSRPBT Star Rating System criteria where they more or less match each other in various ways, thus LOC:SSR-PBT Star Rating System was later used to provide a more systematic, thorough and deeper analysis. Both examination of the extent and nature of LOC and LOC:SSR-PBT Star Rating System implemented in both LGAs studied is observed to be in line. The differences in emphasis justify the nature of MCS which exists and they relate to the achievement of t heir star rating. In understanding the phenomena of change the study uses DiMaggio and Powell’s (1983) framework to look at the institutional isomorphism in terms of the external forces penetrated to affect the change…